THE ROLE OF NATIONAL CULTURAL CENTERS IN UZBEKISTAN IN INTERNATIONAL HARMONY - Davronova Mohigul (American Journals Publishing, 2024)
This article talks about the role of national cultural centers in Uzbekistan in interethnic harmony. The author, relying on scientific data, studied and analyzed the specific aspects of the role of national cultural centers in Uzbekistan in interethnic harmony based on available literature.
Keywords: Uzbekistan, national cultural centers, interethnic harmony.